Representation of Culture and Human Rights Violations in Timothy Wangusa’s Upon This Mountain and Austin Bukenya’s The Bride. Unisa Press. - Tugume, Benon. (Unisa Press, 2025)
This article examines the portrayal of culture and human rights violations in Timothy Wangusa’s novel, Upon This Mountain and Austin Bukenya’s play, The Bride. It focuses on the Bagisu cultural ritual of circumcision in Upon This Mountain as well as the culture-based traditions of prejudice and discrimination in The Bride that are responsible for the violation of the rights of Kangala, Wabwire, and Mwambu in the former, and Namvua and her entire Merio family in the latter. In this article, I apply qualitative methods of data collection and analysis since it is a case study of Wangusa’s Upon This Mountain and Bukenya’s The Bride as primary texts. Data for analysis is generated by carrying out a close reading of the primary texts as well as secondary texts—critical works, journal articles, and literature on human rights purposely to strengthen the discussion of culture and human rights violations depicted in the primary texts. The reading of primary texts focuses on characters and themes since the objectives are twofold: first, to examine the point of view of individual characters subjected to ritual pain, trauma, and intra-cultural discrimination in Upon This Mountain and second, to analyse the writer’s use of dialogue and action to dramatise resistance to cultural prejudices and discrimination in The Bride. Using principles of human rights, the paper discusses the pain, torture, and degrading treatment Kangala and Wabwire in Upon This Mountain go through as they submit to the ritual of the knife. Similarly, the article explores discrimination against Namvua and her entire Merio family based on age-old cultural prejudices in The Bride. Lekindo, the leader of the young generation is opposed to her discrimination and fights for her rights and acceptance in the plains by smashing the skull, an iconic symbol of cultural beliefs. He marries Namvua to underscore the theme of the inevitability of change because of human rights abuses.